The Effectiveness of Creditworthiness Indicators According to The PRISM Model in Granting Credit Decisions: The Modifying Role of the Quality of Accounting Information (Field Study: Jordanian Commercial Banks) - Al-Qudah, Laith Akram; Al-Hroot, Yusuf Ali; Abdel Salam, Ahmed Othman (Jordan Journal of Business Administration, 2022)
The current study aimed at identifying the effectiveness of creditworthiness indicators according to the (PRISM) model with its dimensions (future outlook, ability to pay, the purpose of credit, guarantees and management) in granting credit decisions in Jordanian commercial banks. The study also aimed to demonstrate the role of the quality of accounting information as a modifying variable in enhancing the effectiveness of creditworthiness indicators according to the (PRISM) model in credit granting decisions in Jordanian commercial banks. In order to achieve the objectives of the current study, the researchers have applied the descriptive analytical approach. The study population consisted of all managers, heads of departments and decision-makers in the credit departments of the General Administration of Jordanian Commercial Banks, amounting to (13) commercial banks, where (69.2%) of the study population (9 banks), where 191 employees work, were covered. The study sample consisted of ‎a stratified random sample. (128) questionnaires were distributed to the study sample individuals, 126 of which were retrieved and found to be valid for analysis. Having examined the hypotheses of the current study, the results showed that there was a statistically significant effect for creditworthiness indicators according to the (PRISM) model with its dimensions (future outlook, ability to pay, the purpose of credit and management) in granting credit decisions in Jordanian commercial banks. The results have also revealed that accounting information has modified the effectiveness of creditworthiness indicators according to the (PRISM) model in credit granting decisions in Jordanian commercial banks. The researchers have recommended the departments in the Jordanian commercial banks to study the operating and financing strategies of the customer before granting credit.